PRAKTIKALITAS MODUL PENDIDIKAN SADAR WISATA BAGI PENGELOLA OBJEK WISATA BERBASIS MASYARAKAT DI KABUPATEN AGAM SUMATERA BARAT - Novalita, Rahmi (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2019)
The community, especially the managers of tourism objects has a very strategic role in managing and utilizing the potential of the environment to be cleaner, more orderly, comfortable, safe, beautiful, cool, and memorable. But some of the obstacles faced by community-based tourist managers are namely; first, the lack of knowledge about tourism awareness and the limitations of tourism information in creating a clean, orderly, comfortable, safe, beautiful, cool, and memorable environment. The second is the limitations of teaching materials for community-based tourism managers; the third is the limitations of human resources in providing learning to community-based tourism managers. Purpose the research is The chipper about practicality of tourism awareness education modules used ADDIE models. The type of research is Research and Development (R & D). The number of research subjects is 20 people with the determination of samples made by incidental techniques. Data collection techniques consist of interview guides, questionnaires, observation shees The data analysis technique persentase. The results of the study show that the practicality of tourism awareness education modules for community-based tourism managers is very practical.